Update on rescue therapies in patients with lamivudine-resistant chronic hepatitis B - Chao DC; Hu KQ (Dove Medical Press, 2013)
Daniel C Chao, Ke-Qin HuDivision of Gastroenterology and Hepatology, University of California, Irvine Medical Center, Orange, CA, USAAbstract: Chronic hepatitis B continues to be a global problem, with an estimated 240 million cases according to the World Health Organization. Chronic infection with the hepatitis B virus (HBV) is associated with cirrhosis, hepatic decompensation, and hepatocellular carcinoma. There are currently several US Food and Drug Administration-approved medications for treating chronic hepatitis B, with Lamivudine (LAM) being the first oral agent made available. The major problem with LAM is significantly decreased effectiveness over time due to the development of anti-HBV resistance that can lead to virologic and biochemical breakthrough as well as hepatitis B flare, progression of liver disease, and decompensation of pre-existing cirrhosis. Despite its high anti-HBV resistant rate, LAM remains widely used in underdeveloped countries due to its wide availability and low cost compared to other antiviral medications, including those that are more effective. Therefore, it is still clinically important to learn how to prevent and treat LAM resistant strains of HBV. Several regimens with the other available antiviral agents have been studied, including switching to monotherapy with either Adefovir, Entecavir, or Tenofovir, adding Adefovir to LAM, and switching to a combination of Adefovir and Entecavir. This review article will examine molecular mechanisms and diagnosis of LAM anti-HBV resistance, risks for and approaches to reduce LAM anti-HBV resistance, and currently available rescue therapy regimens for LAM resistance.Keywords: chronic hepatitis B, nucleot(s)ide analogs, anti-viral resistance, lamivudine, adefovir, entecavir, tenofovir